More library mashups : exploring new ways to deliver library data - Engard, Nicole C., 1979- (Information Today, Inc, 2015)
A collection of mashup projects that virtually any library can emulate, customize, and build upon. Discover how to use free and inexpensive digital tools and techniques to improve library services and meet everyday-- and unexpected-- challenges.--